Etika Dan Batasan Hukum Dalam Perang : Analisis Terhadap Kejahatan Humaniter Dalam Fiqih Siyasah - Nanda Muntazza; Askana Fikriana (LPPM Universitas Sains dan Teknologi Komputer, 2023)
This in-depth study discusses the ethical aspects and legal limitations related to warfare from the perspective of fiqh siyasah. The research method employed is a literature review, drawing upon sources such as books, journals, and relevant articles. The primary objective of this research is to delve into a comprehensive understanding of the rules and ethics of war within the framework of international law. The main findings highlight the significance of Humanitarian Law as a branch of international public law that governs armed conflicts worldwide, aiming to ensure that war is conducted within a legal framework that respects humanitarian principles. Islamic teachings provide clear guidance on how to engage in warfare with due consideration for the protection of civilian populations and the avoidance of humanitarian crimes, prohibiting indiscriminate attacks and arbitrary acts of violence against civilian populations. By adhering to these principles, Muslim armies can fulfill their duties in war with integrity and respect for high humanitarian values, thus making a significant contribution to understanding the role of ethics and law in the context of warfare, especially from the perspective of fiqh siyasah.